Performance of CFRP-confined concrete cylinder specimens - laboratory study - Golubka Nechevska-Cvetanovska; Artur Roshi; Jordan Bojadjiev; Julijana Bojadjieva; Zoran Trajcevski (Građevinar)
The research presented in this paper focuses on the application of innovative materials for the repair and strengthening of RC columns of buildings in seismically active regions. The analytical and laboratory research for defining the compressive strength and elastic modulus of concrete cylinders confined with CFRP (Fibre Reinforced Polymers) was carried out at the Skopje-based Institute of Earthquake Engineering and Engineering Seismology – IZIIS in order to present the possibilities and benefits of using these materials. Selected results from laboratory testing of built-in materials, and some analytical results from the designed CFRP-confined RC columns for quasi static tests, are presented in this paper.